The multiple functions and mechanisms of osteopontin - Icer, Mehmet Arif; Gezmen-Karadag, Makbule (Clinical biochemistry, 2018)
Osteopontin (OPN) is a highly phosphorylated glycophosphoprotein having acidic characteristics and rich in aspartic acid. OPN, a multifunctional protein, has important functions on cardiovascular diseases, cancer, diabetes and kidney stone diseases and in the process of inflammation, biomineralization, cell viability and wound healing. Osteopontin acts on organisms by playing a key role in secretion levels of interleukin-10 (IL-10), interleukin-12 (IL-12), interleukin-3 (IL–3), interferon-γ (IFN-γ), integrin αvB3, nuclear factor kappa B (NF-kB), macrophage and T cells, regulating the osteoclast function and affecting CD44 receptors. The aim of the present review is to address majority of different functions of OPN protein which are known, suspected or suggested through the data obtained about this protein yet. [Display omitted] •Osteopontin is a significant chemical attractant for macrophages and T cells.•Osteopontin reduce the risk of bone fractures through the different mechanisms.•Osteopontin increases risk of atherosclerotic plaque formation leading to calcification in arteries.•Plasma osteopontin levels correlate with tumor necrosis factor-α (TNF-α) secretion.•Use of urinary osteopontin level may be considered as a biochemical parameter to diagnose the risk of stone formation.